Comparing size selectivity of traditional and knotless diamond-mesh codends in the Iceland redfish (Sebastes spp.) fishery - Cheng, Zhaohai; Einarsson, Haraldur Arnar; Bayse, Shannon; Herrmann, Bent; Winger, Paul (Fisheries Research, 2019)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. . Published version available at https://doi.org/10.1016/j.fishres.2019.04.009. The size selectivity and usability of two diamond mesh codends, a traditional two-panel codend versus an experimental four-panel ultra-cross knotless mesh codend, were compared using the covered codend method in the Iceland redfish ( Sebastes norvegicus and S. viviparous ) fishery. Results showed that there was no significant difference in size selectivity between the codends at lengths greater than 29 cm for S. norvegicus and 19 cm for S. viviparous . At smaller lengths, size selectivity was undetermined due to small catches at those sizes. For S. norvegicus , both codends demonstrated a high retention ratio (93.4 and 92.9%, respectively) above the minimum reference length (MRL; 33 cm), but also had a high retention below MRL (90.9 and 83.4%, respectively). However, the actual proportion of catch below MRL was low due to few small fish on fishing grounds. Since these fish are difficult to tell apart and have similar morphologies, we investigated the size selectivity of the two codends for both species combined, resulting in similar results of no difference in size selectivity, but a large increase in actual catches below MRL, which were primarily S. viviparous . This study concludes that the experimental codend does not improve the size selectivity or usability in the Iceland redfish fishery and both codends will retain large proportions of undersized fish if present on fishing grounds; however, few undersized fish were present in the study area.